Comment to: Core training promises more than it can hold: A review of current literature and practical experience - Atle Hole Sæterbakken; Vidar Andersen (Fysioterapeuten, 2022)
Introduction: In sport, core training has been used as a supplement to traditional training modalities. The scientific literature has significantly increased the last decade whereas core training has been embraced and conceptualized among clinicians, the fitness industry, exercise enthusiasts, and in sport.